Economic geography within and between European nations : the role of market potential and density across space and time - Steven Brakman; Harry Garretsen; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2009)
In explaining the uneven spatial distribution of economic activity, urban economics and new economic geography (NEG) dominate recent research in economics. A main difference between these two approaches is that NEG stresses the role of spatial linkages whereas urban economics does not do so. We estimate simple versions of these two views on economic geography and also establish if the relevance of spatial linkages varies across aggregation levels or time. For our sample of 14 European countries and 213 corresponding regions, we find that spatial linkages are more important at the country level and that its relevance varies across time.
Keywords: F12; F13; R11; R15; 330; Regionale Disparität; Neue ökonomische Geographie; Stadtökonomik; Räumliche Interaktion; EU-Staaten